Long-Term Survival in 241 Cases of Intussusception in Cattle and Factors Associated with Mortality - Laurens Chantillon; Mathilde Laetitia Pas; Lieven Vlaminck; Bart Pardon (Animals, 2024)
Intussusception is a frequent cause of mechanical ileus in cattle. Long-term survival has never been described and risk factors for mortality are scarcely documented. A retrospective cohort study on 241 cattle was conducted to determine survival of intussusception and identify risk factors for mortality. Clinical records were matched with the national cattle identification database. Information on possible predictors including clinical examination, ultrasonography, blood-gas analysis and surgery were collected. Survival analysis and decision tree analysis were used. Overall survival was 44.8% until discharge. Of all animals, 39.0% could complete their life cycle and were eligible for slaughter. Male animals and cattle < 226 days old experienced a significantly higher mortality risk (hazard ratio [HR] = 2.1; 95% confidence interval [CI] = 1.4–3.0 and HR = 2.4; 95% CI = 1.7–3.4, respectively). The final model consisted of heart rate (>95 beats per minute) and packed cell volume (<36.5%) with sensitivity and specificity of 60.4% and 49.4%, respectively. A second model consisted of sex (male) and time to referral (>4.5 days) with sensitivity and specificity of 88.0% and 65.6%, respectively. The long-term prognosis for intussusception in cattle appears to be fair. Factors identified in this study may aid in the decision-making process in cases with presumed intussusception to perform the surgery or opt for euthanasia.